Counseling the unemployed: does it lower unemployment duration and recurrence? - Bruno Crépon; Muriel Dejemeppe; Marc Gurgand (Institute for the Study of Labor (IZA), 2005)
This article evaluates the effects of intensive counseling schemes that are provided to about 20% of the unemployed since the 2001 French unemployment policy reform (PARE). Several of the schemes are dedicated at improving the quality of assignment of workers to jobs. As a result, it is necessary to assess their impact on unemployment recurrence as well as unemployment duration. Using duration models and a very rich data set, we can identify heterogenous and time-dependent causal effects of the schemes. We find significant favorable effects on both outcomes, but the impact on unemployment recurrence is stronger than on unemployment duration. In particular, the program shifts the incidence of recurrence, one year after employment, from 33 to 26%. This illustrates that labor market policies evaluations that consider unemployment duration alone can be misleading.
Keywords: J64; J68; 330; unemployment duration; employment duration; active labor market policy; counseling; Arbeitsvermittlung; Arbeitslosigkeit; Arbeitsuche; Frankreich